Differences in microleakage in bulk-fill composite resin and fiber reinforced composite restorations in class I cavities with the bulk-fill technique - Verawati Ashari; Gita Tarigan; Wilvia Wilvia (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2018)
Introduction: Micro leakage is one of the most frequent failures of old restorations and new restorations. Many factors can cause micro leakage among other types of restorative materials. Addition of fiber into the resin is said to increase resistance to fracture and strengthen restorations and reduce micro leakage than fiberless resins. Objective: To know the difference of micro leakage on bulk-fill composite resin and fiber reinforced composite materials in class I cavity by bulk-fill technique. Method: pure experimental study, the sample in this study used post-extraction molar teeth of 32 free from caries. The sample was first soaked a 0.9% NaCl solution for 1 day to condition the teeth in the mouth, then sample will be done cavity class I preparation and will be restored with two different restorative materials. After the restoration will be done soaking on 2% methylene blue liquor for 1 day, after that thermocycling process with temperature 5˚ and 55˚, after that cutting and observation of micro leak with stereomicroscope Result: Average of micro leakage happened more large on bulk-fill composite resin compared with fiber reinforced composite. with p value = 0.000 (p <0,05). Conclusions: The average micro leakage occurring is greater in composite bulk-fill resins than with composite reinforced fiber composite resins. Micro leakage that occurs smaller in composite resin fiber resin than composite bulk-fill resin due to differences in composite resin content.